2013
DOI: 10.1161/circulationaha.113.002937
|View full text |Cite
|
Sign up to set email alerts
|

Cocaine-Induced Vasoconstriction in the Human Coronary Microcirculation

Abstract: Background Cocaine is a major cause of acute coronary syndrome (ACS), especially in young adults; however, the mechanistic underpinning of cocaine-induced ACS remains limited. Previous studies in animals and in patients undergoing cardiac catheterization suggest that cocaine constricts coronary microvessels, yet direct evidence is lacking. Methods and Results We used myocardial contrast echocardiography (MCE) to test the hypothesis that cocaine causes vasoconstriction in the human coronary microcirculation. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 55 publications
(53 reference statements)
1
18
0
2
Order By: Relevance
“…Consistent with the known effects of cocaine on the sympathetic nervous system, cardiomyocytes, and vasculature, recent work using myocardial contrast echocardiography clearly demonstrated that cocaine use resulted in a sizeable decrease in myocardial perfusion and decreased myocardial capillary blood volume in otherwise healthy, cocaine-naive young men [31]. Over time, with ongoing cocaine use hypertension, aortic stiffness, left ventricular mass, and other measures of adverse cardiovascular dynamics progressively worsen in otherwise healthy young individuals [32][33][34].…”
Section: Imaging Evidencementioning
confidence: 71%
See 1 more Smart Citation
“…Consistent with the known effects of cocaine on the sympathetic nervous system, cardiomyocytes, and vasculature, recent work using myocardial contrast echocardiography clearly demonstrated that cocaine use resulted in a sizeable decrease in myocardial perfusion and decreased myocardial capillary blood volume in otherwise healthy, cocaine-naive young men [31]. Over time, with ongoing cocaine use hypertension, aortic stiffness, left ventricular mass, and other measures of adverse cardiovascular dynamics progressively worsen in otherwise healthy young individuals [32][33][34].…”
Section: Imaging Evidencementioning
confidence: 71%
“…As described above, the clinical consequences of cocaine use in the short-term include increased myocardial oxygen demand with concomitant decrease in myocardial oxygen supply as well as a demonstrable decrease in myocardial perfusion and decreased myocardial capillary blood volume in otherwise healthy, cocaine-naive young men [31]. Immediately following cocaine use, cocaine-associated chest pain is particularly common and in some may seem ischemic in nature, characterized by pain that is substernal and pressurelike, while in others, the pain seems to have a pleuritic component [10].…”
Section: Short-term Cardiovascular Consequencesmentioning
confidence: 99%
“…dobutamine in both dogs 23 and young men. 14 Although CO is a direct coronary vasodilator, 12 the mechanism of the increase in myocardial blood flow with acute CO inhalation is mainly capillary recruitment, 24 causing increased myocardial blood volume with unchanged myocardial blood flow velocity—the opposite pattern of microvascular response to what we saw with hookah smoking.…”
Section: Discussionmentioning
confidence: 81%
“…infusion of lipid-shelled perflutren-containing microbubbles by one experienced sonographer (XT) as previously described, using proved methods to minimize variability. 14,15 Contrast-enhanced 2-dimensional transthoracic echocardiography was performed using a phased-array probe interfaced with an imaging system (iE33; Philips Medical Systems, Andover, Massachusetts). One vial (1.3 ml) of lipid-shell octafluoropropane microbubbles (Definity; Lantheus Medical Imaging, North Billerica, Massachusetts) was diluted to a total volume of 30 ml in normal saline solution and administered intravenously with an infusion pump (Medfusion 3500 Syringe Pump; Smiths Medical ASD Inc, St. Paul, Minnesota) at a rate of 1.0 ml/min.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation